Diagnostic Yield of Transu rethral resection of prostatetransu rethral r esection of bladder tumor TURP and(TURBT) in Mosul Two Years Study - S. Hassan, Intisar; Y. Suleiman, Abdulkarem; A. Hassawi, Bashar (Tikrit Journal of Pharmaceutical Sciences, 2023)
Yield of TURP-TURBT (lransurethral resection of prostate transurethmal resection of bladder tumor) in Mosul has not been studied before. Prostatic & bladder cancers are increasing in this specific locality, to know their frequency and grades this study was donc. Four hundred and ninety TURP-TURBT chips were received, examined grossly, processed routinely, and then analyzed microscopically. The study was performed in Alzahrawi hospital - histopathology laboratories of Mosul city in Iraq between January 2006 and through December 2007. There were 320 (65.3%) were taken hy TURP and 170 (34.7%): were taken by TURBT (142 male and 28 female). Benign prostatic hyperplasia was the predominant TURP finding (282; 88.1% cases), while prostatic carcinoma was found in 38 (11.9%) cases. Most of the prostale cancer cases were received as high grades (Gleason's grade 4 and 5). Transitional cell carcinoma was the chief TURBT finding (149; 87.6'%). prostatic carcinoma and transitional cell carcinoma are common in this locality. Most cases of prostate carcinoma were diagnosed as high grades.